Expression of a SOX1 overlapping transcript in neural differentiation and cancer models - Azaz, Ahmad; Strohbuecker, Stephanie; Tufarelli, Cristina; Sottile, Virginie (Springer, 2017)
SOX1 is a member of the SOXB1 subgroup of transcription factors involved in early embryogenesis, CNS development and maintenance of neural stem cells. The structure and regulation of the human SOX1 locus has been less studied than that of SOX2, another member of the SOXB1 subgroup for which an overlapping transcript has been reported. Here we report that the SOX1 locus harbours a SOX1 overlapping transcript (SOX1-OT), and describe expression, splicing variants and detection of SOX1-OT in different stem and cancer cells. RT-PCR and RACE experiments were performed to detect and characterize the structure of SOX1-OT in neuroprogenitor cultures and across different cancer cell lines. SOX1-OT was found to present a complex structure including several unannotated exons, different transcript variants, and at least two potential transcription start sites. SOX1-OT was found to be highly expressed in differentiated neural stem cells across different time points of differentiation, and its expression correlated with SOX1 gene expression. Concomitant expression of SOX1 and SOX1-OT was further observed in several cancer cell models. While the function of this transcript is unknown, the regulatory role reported for other lncRNAs strongly suggests a possible role for SOX1-OT in regulating SOX1 expression, as previously observed for SOX2. The elucidation of the genetic and regulatory context governing SOX1 expression will contribute to clarifying its role in stem cell differentiation and tumorigenesis.